Should all drugs be legalized?: a primer for the 21st century - Busby, Mattha (The Big Idea, 2022)
Combining a unique visual approach with carefully constructed narrative text, this book provides a survey of the history of drug use, a review of the impact of the war on drugs, an appraisal of the effects of legal vs illegal drugs and an evaluation of the impact of the decriminalization of drugs.0 According to archaeological and historical records, ethanol in the form of beer in Sumeria and wine in Egypt has been used recreationally for 13,000 years, while psychotropic drugs have been used for thousands of years, mainly for religious purposes. This book sets out the history of the use of drugs since the Neolithic age, and explores the evolution of recreational drug use from the mid-18th century on. It considers the lethal and social impact of heavy use of legal alcohol or nicotine vs the hazards to health and society associated with illegal drugs. It evaluates the effects of the 50-year failed global war on drugs on the criminal production and trafficking of drugs on the black market and on the abuse, health and imprisonment of end users. Finally, it argues for the decriminalization of all drugs and the state regulation of the drug market, with suitable controls and regulation for each drug type